Interpretation of results obtained using real-time fluorescence PCR based on multiplex PCR fragment analysis for ABCB1 tri-allele - Zhang Yan; Meng Zhuocheng; Xing Huan; Cui Xiaohua; Yang Liu; Zheng Xuan; Dai Zunxiao (Sichuan jingshen weisheng, 2022)
ObjectiveTo resolve the problems related to the abnormal interpretations of real-time fluorescence polymerase chain reaction （PCR） results for tri-allele， to formulate the interpretation methods of real-time fluorescence PCR by referring to multiplex PCR fragment analysis， so as to obtain an accurate， simple and cheap detection method for ABCB1 tri-allele.MethodsA total of 2 794 DNA samples were collected from Xi'an Mental Health Center from March 2020 to March 2021， and 5% of which were selected as experiments. Real-time fluorescence PCR method and multiplex PCR fragment analysis method were performed respectively. According to the comparison of Ct values of PCR curves and the comparison of base peak intensity in multiplex PCR fragment analysis， comparison and analysis were conducted on the interpretation results of the two methods， and samples with different interpretation results were verified， thereafter， PCR interpretation method was formulated.ResultsA total of 139 samples were collected， of which 120 alleles and 19 tri-allele were detected. The results of allele detection by two methods were absolutely consistent. In combination with the results of multiplex PCR fragment analysis， a method for the interpretation of real-time fluorescence PCR for 19 cases of tri-allele was developed as follows： when ∣∣Ct.G－Ct.T∣－∣Ct.G－Ct.A∣∣ in amplification curve was less than 3， the interpretation results were the combination of the base pairs with small Ct values； when ∣∣Ct.G－Ct.T∣－∣Ct.G－Ct.A∣∣ was greater than or equal to 3， the interpretation results were homozygotes from the base pairs with minimum Ct values. According to the interpretation method， the results of real-time fluorescence PCR were revised， and it showed 1 case of G/G， 1 case of A/A， 4 cases of T/G， 5 cases of T/A and 8 cases of T/T， which were consistent with the results of multiplex PCR fragment analysis.ConclusionReferring to the multiplex PCR fragment analysis method， the interpretation of ABCB1 tri-allele by real-time fluorescence PCR is developed， and the two interpretation methods are in good agreement.